Heuristics and decision rationality in entry mode choice: Implications for decision effectiveness and international performance - Faroque, Anisur R.; Rahman, Arafat; Gani, Mohammad Osman; Hoque, Imranul (Elsevier, 2025)
This study explores how heuristics (availability and representativeness) and analytic rational decision-making influence the selection of international business entry modes and their subsequent impact on decision effectiveness and international performance. Grounded in dual-process theories, the research develops hypotheses linking heuristics, analytic rationality, decision effectiveness, and international outcomes. Utilizing a quantitative survey approach, the findings reveal that integrating the availability heuristic with analytic rational decision-making enhances the quality of internationalization decisions, whereas combining analytic decision-making with the representativeness heuristic can diminish decision effectiveness. These results emphasize the critical role of balancing heuristic and analytical approaches in managerial decision-making for international entry, contributing to dual-process theories within the international business context and providing valuable insights into the cognitive strategies shaping entry mode selection and organizational performance.
Keywords: Heuristics; Decision rationality; Dual process theory; Decision effectiveness; Entry mode; Performance; International Business; Kansainvälinen liiketoiminta